LOTUS: Protocol for a double-blind placebo controlled randomized trial of hemp-derived cannabidiol for the treatment of cannabis use disorder. - L Cinnamon Bidwell; Renee Martin-Willett; Samantha N Melendez; Luiza Rosa; Gregory Giordano; Kent E Hutchison; Angela D Bryan (PLoS ONE)
Background As cannabis legalization continues to spread across the United States, average Δ9-tetrahydrocannabinol concentrations in recreational products have significantly increased, and no prior study has evaluated effective treatments to reduce cannabis use among high potency cannabis users. Some research has found that the non-intoxicating cannabinoid cannabidiol reduces cannabis use and cannabis use disorder-related symptoms, such as affective disturbance and withdrawal. Results of these studies are promising but limited to synthetic or isolated forms of cannabidiol. Objective Conduct a placebo-controlled randomized control trial comparing the effects of hemp-derived cannabidiol on reducing Δ9-tetrahydrocannabinol use in concentrate users with cannabis use disorder. Methods Design. Double-blind, three-arm randomized placebo-controlled trial. Setting. University in the Denver-Boulder, CO, USA area. Study population. Community members who are heavy, stable cannabis concentrate users that meet criteria for at least moderate cannabis use disorder and are seeking to decrease or stop cannabis use. Data. Self-report demographics, substance use, and mental health characteristics, blood and urine based biomarkers and anthropometrics. Outcomes. Affective, physiological, and physical withdrawal symptoms, Δ9-tetrahydrocannabinol use. Analysis. Three-group ANOVAs and χ2 tests will be used to compare baseline variables between groups. Characteristics that differ between groups will be evaluated as potential covariates in subsequent analyses. A multilevel modeling framework will be used for primary outcome analysis to account for the repeated observations nested within participants over time. Pairwise post-hoc simple effects tests will be conducted to confirm patterns of differences. Trial registration ClinicalTrials.gov NCT06107062.